Early Life Stress-Induced Epigenetic Programming of Hippocampal NPY-Y2 Receptor Gene Expression Changes in Response to Adult Stress - Kocamaz, Derya; Franzke, Caroline; Gröger, Nicole; Braun, Katharina; Bock, Jörg (Frontiers in Cellular Neuroscience, 2022)
Early Life Stress (ELS) can critically influence brain development and future stress responses and thus represents an important risk factor for mental health and disease. Neuropeptide Y (NPY) is discussed to be a key mediator of resilient vs. vulnerable adaptations and specifically, the NPY-Y2 receptor (Y2R) may be involved in the pathophysiology of depression due to its negative regulation of NPY-release. The present study addressed the hypotheses that ELS and adult stress (AS) affect the expression of hippocampal Y2R and that exposure to ELS induces an epigenetically mediated programming effect towards a consecutive stress exposure in adulthood. The specific aims were to investigate if (i) ELS or AS as single stressors induce changes in Y2 receptor gene expression in the hippocampus, (ii) the predicted Y2R changes are epigenetically mediated via promoter-specific DNA-methylation, (iii) the ELS-induced epigenetic changes exert a programming effect on Y2R gene expression changes in response to AS, and finally (iv) if the predicted alterations are sex-specific. Animals were assigned to the following experimental groups: (1) non-stressed controls (CON), (2) only ELS exposure (ELS), (3) only adult stress exposure (CON+AS), and (4) exposure to ELS followed by AS (ELS+AS). Using repeated maternal separation in mice as an ELS and swim stress as an AS we found that both stressors affected Y2R gene expression in the hippocampus of male mice but not in females. Specifically, upregulated expression was found in the CON+AS group. In addition, exposure to both stressors ELS+AS significantly reduced Y2R gene expression when compared to CON+AS. The changes in Y2R expression were paralleled by altered DNA-methylation patterns at the Y2R promoter, specifically, a decrease in mean DNA-methylation in the CON+AS males compared to the non-AS exposed groups and an increase in the ELS+AS males compared to the CON+AS males. Also, a strong negative correlation of mean DNA-methylation with Y2R expression was found. Detailed CpG-site-specific analysis of DNA-methylation revealed that ELS induced increased DNA-methylation only at specific CpG-sites within the Y2R promoter. It is tempting to speculate that these ELS-induced CpG-site-specific changes represent a “buffering” programming effect against elevations of Y2R expression induced by AS.